Studies on neuroinvasion, susceptibility and long-term persistence of alphaherpesviruses in the murine central nervous system - Korff, Viktoria; Justus Liebig University Giessen (My University, 2025)
Alphaherpesviruses such as HSV-1 and PrV exhibit pronounced neurotropism and the ability to establish acute and latent infections within the nervous system. To elucidate key determinants of alphaherpesviral neuroinvasion and persistence, this thesis employed the attenuated mutant PrV-ΔUL21/US3Δkin in CD-1 mice, which reproduces hallmark features of human HSE. Through a combination of targeted stereotactic and intranasal infection models, three principal aspects were addressed: (i) regional and cell type–specific neuronal susceptibility, (ii) anatomical pathways of early CNS entry, and (iii) long-term infection dynamics including latency and reactivation. The studies identified the mesial temporal, piriform, and prefrontal cortices as core targets, linked to high nectin-1 expression and specific anatomical connectivity. Neuroanatomical mapping revealed that PrV gains CNS access via a multimodal cranial-nerve network encompassing trigeminal, olfactory, glossopharyngeal-vagal, and hypoglossal routes converging in the brainstem. Long-term analyses demonstrated persistent, low-grade infection and episodic abortive or subclinical reactivation associated with neuroinflammatory responses, indicating a predominantly central establishment of viral latency that extends the current understanding of alphaherpesviral persistence to include central neuronal reservoirs in addition to peripheral ganglia. Collectively, these findings establish the PrV-ΔUL21/US3Δkin model as a robust and translationally relevant system for dissecting regional and receptor-dependent neurotropism, multimodal cranial-nerve-mediated CNS entry, and the central dynamics of alphaherpesviral latency and reactivation.
Keywords: Neuroscience; ddc:630